(3JSgjd GdahGFO hJcejd GdebGUOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3YHO GdNGdb Hf Ydi Hf GdaQGJ s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe gPG cJGH ai GdfMh LYdJg HYhf Gddg eSJhajkG dGUhdg eSJhdjkG Ydi CHhGHg haUhdg s
(3BNQgG (B:s
(3aUd RjOJ Cda ai eGjg heG jJjf hHYO hdh GdLeY GdeJWQaI GdeJUdI hgPG eeG jfbGO Edjg hdG jbGS Ydjg Je s
(3GdfSNI HgG MhGTs
(3HChdgG ELGRI HGdcJGH ef GdTjN MSf eMeO GdYWGQ dTjN GdESdGe CMeO YGQa MceJ RGOgs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs